DEMONSTRATION OF DEPRESSANT EFFECT OF PROPRANOLOL AND ACEBUTOLOL ON THE CONTRACTILE RESPONSE OF RAT ISOLATED DIAPHRAGM WITH ELECTRICAL STIMULATION - Nawaz, Shah; Din, Jalal -ud-; Ahmed, Qazi Rashid; Khan, Tahir Saleem; Jan, Muhammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: Propranolol is a non-selective, while acebutolol is a cardioselective beta blocker. This study was designed to implore into the effect of nonselective and cardioselective beta blockers on the electrically stimulated contractile response of isolated diaphragm of rat. Methods: Study was conducted on male and female rats of albino variety, weighing 150-200 grams, in Jinnah Postgraduate Medical Centre Karachi. Diaphragmatic strips were prepared. Tissue was transferred to a tissue bath containing oxygenated Krebs solution kept at 32°C. One end of the strip was connected to the electrodes of an electric stimulator, while its other end was connected to a polygraph through a force displacement transducer. Normal recordings of the response of tissue to electrical stimulation was obtained. The response was observed with 10-8 - 10-3 M concentrations of propranolol and acebutolol separately and in series. Contractile response of the tissue was measured in millimeters. Arithmetic mean for each set of observation was determined. T test was performed and P value was determined from the t table Results: Both propranolol and acebutolol produced significant depression of the contraction of rat isolated diaphragm as a result of electrical stimulation. Conclusion: Our study has shown that the depressant effect of beta adrenoceptor blocking drugs. perhaps, do not play important role in the etiology of respiratory distress produced by these drugs, because the depressant effect of both propranolol and acebutolol on diaphragm are only produced in high doses.